The construction of ethnoreligious identity among Muslims and Christians in Rote Ndao Regency, Indonesia - Pandie, Daud; Lattu, Izak YM; Suwarto, Suwarto; Lukmono, Lobby (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
There has been much research on the violent conflict in interactions between ethnic and religious communities in Indonesia. However, there is a noticeable gap in research focusing on how people can live harmoniously across these divides. This paper aims to explore the construction of ethnoreligious identity in Christian-Islamic encounters in Rote Ndao Regency, Indonesia. The fundamental question underlying this research is how the socio-historical and cultural backdrop contributes to forming 'Rote Islam' as an ethnoreligious identity and how processes of interaction, negotiation, and integration shape social interactions between Christians and Muslims. The research employs an ethnographic and phenomenological approach incorporating observations, interviews, participation, and literature studies to achieve this. The findings indicate that as an ethnoreligious identity, ‘Rote Islam’ is constructed from a process of interaction and social practice (collaborative) that has gone beyond religious and cultural boundaries. Examples of these practices include the gifting of land, the transformation of kinship through marriage, the transfer of technology, the tradition of kissing noses, the Kebalai dance, the celebration of religious holidays, and the identification of Leo, all of which illustrate the processes described in this study.